Pengaruh Pelatihan Kerja dan Komitmen Organisasional terhadap Turnover Intention Karyawan : PT. Angkasa Pura I (Persero) Kantor Cabang Bandar Udara Internasional Sam Ratulangi Manado - Pangau, Gabriella Y.; Rumawas, Wehelmina; Walangitan, Olivia F. C. (Productivity, 2023)
This research aims to determine the effect of job training and organizational commitment on PT employee turnover intention. Angkasa Pura I (PERSERO) Sam Ratulangi Manado International Airport Branch Office. The type of research used is quantitative research, with data collection methods using survey methods, namely questionnaires. This research used a sample of 50 respondents. The researcher used the statistical data analysis method of structural equation modelling (Structural Equation Modeling). Managed the data using smart PLS software. From the results of the research and discussion, it was concluded that the job training variable had a positive and significant direct influence on the organizational commitment variable, the job training variable had a negative and significant direct influence on the turnover intention variable, the organizational commitment variable had a negative and significant direct influence on turnover intention variable, the job training variable has a significant indirect influence on the turnover intention variable through organizational commitment, this can be seen from the partial test results.